Adherence, persistence, glycaemic control and costs among patients with type 2 diabetes initiating dulaglutide compared with liraglutide or exenatide once weekly at 12‐month follow‐up in a real‐world setting in the United States. Issue 4 (9th January 2019) - Mody, Reema; Huang, Qing; Yu, Maria; Zhao, Ruizhi; Patel, Hiren; Grabner, Michael; Landó, Laura Fernández
Abstract : Aims: To evaluate adherence, persistence, glycaemic control and costs at 12‐month follow‐up for patients initiating dulaglutide versus liraglutide or exenatide once weekly. Materials and methods: The present retrospective observational claims study included patients with type 2 diabetes (T2D) and ≥ 1 pharmacy claim for dulaglutide, liraglutide or exenatide once weekly from the HealthCore Integrated Research Database. Adherence was defined as proportion of days covered ≥80%, and persistence was measured by time to discontinuation of index therapy. Change from baseline in glycated haemoglobin (HbA1c) concentration was assessed in a subset with pre‐ and post‐index HbA1c results. Propensity scores were used to match the cohorts. Results: The baseline characteristics were balanced for the matched cohorts, dulaglutide versus liraglutide (n = 2471) and dulaglutide versus exenatide once weekly (n = 1891). Among those initiating dulaglutide there was a significantly higher proportion of adherent patients compared with the groups initiating liraglutide (51.2% vs. 38.2%; P  < 0.001) and exenatide once weekly (50.7% vs. 31.9%; P  < 0.001). At 12 months, 55% of patients in the dulaglutide group versus 43.8% in the liraglutide group ( P  < 0.001), and 54.9% in the dulaglutide versus 34.4% in the exenatide once‐weekly group ( P  < 0.001) were persistent. The dulaglutide group had a significantly greater reduction in HbA1c than the liraglutide group (−34.24 vs. −31.94 mmol/mol; P  = 0.032), and a greater, but nonsignificant, reduction in HbA1c than the exenatide once‐weekly group (−34.46 vs. −31.94 mmol/mol; P  = 0.056). The diabetes‐related total costs were not significantly different between the dulaglutide and the liraglutide group ($16, 174 vs. $16, 694; P  = 0.184), and were significantly higher for dulaglutide than for exenatide once weekly ($15, 768 vs. $14, 615; P  = 0.005). Conclusions: Adherence and persistence are important considerations in patient‐centric treatment selection for patients with T2D. Higher adherence and persistence for dulaglutide compared with liraglutide or exenatide once weekly are relevant criteria when choosing glucagon‐like peptide‐1 receptor agonist treatment for patients with T2D.